MITIGASI KONFLIK ORANGUTAN SUMATERA (Pongo abelii) DENGAN MASYARAKAT DI SEKITAR TAMAN NASIONAL GUNUNG LEUSER - Fitra Dewi Warti Lubis; Yunus Afifuddin; Pindi Patana (Peronema Forestry Science Journal, 2014)
The study, entitled "The Mitigation of Sumatran Orangutan (Pongo abelii) Conflict with Communities Around the Gunung Leuser National Park" was conducted in January- April 2013. The purpose of this study is to determine the implementation of the mitigation efforts that troubled orangutan conflict with society and evaluate mitigation methods that have been done.  This study uses purposive sampling method by interviewing farmers whose farm affected by conflict with orangutan.The evaluation method of conflict mitigation was mostly by traditional method, making noises with firecrackers to dispel orangutans from the field, throwing twigs of trees and report on corps unit, and translocating under conditions critical to the orangutan. Of the two villages that became the object of research, the public never caught or killed orangutans disturbing field. This study shows the role of government and NGOs in dissemination orangutan as animals that must be protected.Key words: Orangutan, conflict mitigation, Gunung Leuser National Park